A novel approach based on journal coupling to determine authors who are most likely to be part of the same invisible college - Garcia Jose A.; Rodriguez-Sanchez Rosa; Fdez-Valdivia J. (Journal of Data and Information Science)
In this paper, we use author clustering based on journal coupling (i.e., shared academic journals) to determine researchers who have the same scientific interests and similar conceptual frameworks. The basic assumption is that authors who publish in the same academic journals are more likely to share similar conceptual frameworks and interests than those who never publish in the same venues. Therefore, they are more likely to be part of the same invisible college (i.e., authors in this subgroup contribute materially to research on the same topic and often publish their work in similar publication venues).